Additive effect of apicidin and doxorubicin in sulfatase 1 (SULF1)-expressing hepatocellular carcinoma in vitro and in vivo - Lai, Jin-Ping (2009)
BACKGROUND/AIMS: There are limited chemotherapy options for hepatocellular carcinoma (HCC). The heparin-degrading endosulfatase SULF1 functions as a liver tumor suppressor. We investigated the effects of the histone deacetylase inhibitor apicidin in combination with doxorubicin in SULF1-expressing HCC cells in vitro and in SULF1-expressing xenografts in nude mice. METHODS: We evaluated the effects of apicidin alone or combined with doxorubicin on apoptosis, caspase activity, and phosphorylation of Erk and Akt in SULF1-transfected Huh7 and Hep3B cells in vitro and in vivo. RESULTS: Apicidin induced HCC cell apoptosis and caspase activation in a dose- and time-dependent manner. Apicidin-induced caspase activation was significantly inhibited by the caspase inhibitor Z-Vad-fmk. Apicidin also decreased phosphorylation of both Erk and Akt. Expression of constitutively-active Mek1 and Akt significantly decreased apicidin-induced apoptosis. The combination of doxorubicin with apicidin significantly increased the anti-tumor effect in the SULF1-expressing Huh7 and Hep3B cells as compared to either apicidin or doxorubicin alone, both in vitro and in vivo. CONCLUSIONS: The combination of a histone deacetylase inhibitor with doxorubicin may be a novel and promising therapeutic modality for HCCs, particularly for SULF1-expressing HCCs.